(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Background: The assessment of lung function in children with asthma is not routinely performed. The use of spirometry in children is difficult to be apply in this age group because it requires active cooperation with forceful expiration; therefore, the use of the forced oscillation technique resolved this problem. Patients and method: This cross-sectional study included 80 children with asthma who were regarded as the patient group and were compared with 80 healthy children as the control group. It was performed in the period from in the period from April 2023 to May 2024. Pulmonary function in both groups was tested using forced oscillation technique. Respiratory resistance (Rrs) and reactance (Xrs) were measured at 5 Hz, and 19 Hz. Results: The mean age of asthmatic children was 6.66 years, and the means of weight, height, and body mass index were 26.36±9.8, 120.75±14.005, 17.58±3.6, respectively. There were highly significant differences between them according to Rrs5, Rrs19, Xrs5,Xrs19, and expiratory flow limitation. The study also showed a significant correlation between weight, height, and body mass index with some forced oscillation technique parameters (Rrs5hzex, Rrs19hzex, Xrs5hz, and Xrs19hz). Simulated ROC analysis confirmed the clinical utility of the forced oscillation technique. Expiratory flow limitation and Rrs5 showed excellent diagnostic performance (AUC > 0.85); with high sensitivity and specificity at the optimal cut-offs values. Conclusions: From the results of this study, we conclude that the forced oscillation technique seems to be an important instrument in the assessment of asthma in children, and we can depend on the values of expiratory flow limitation in determining disease severity. Therefore, further studies are warranted.